Development of Blended Instructional System Using Problem-based Learning to Enhance Higher Thinking Skills and Problem-Solving Ability in Science for Secondary School Students (International Journal of Psychosocial Rehabilitation, 2020)
This study is a research and development project, divided into four phases, each of which has its own objective. The first phase’s objective is to identify the current situation and need of teachers in relation to blended instruction and learning management using problem-based learning to enhance higher thinking skills and problem solving ability in science for secondary school students based on related literature and questionnaire regarding current situation of and need for instruction using problem-based learning to enhance higher thinking skills and problem solving ability in science. The second phase’s objective is to develop a blended instructional system by using data collected from the interviews with nine experts. The third phase’s objective is to determine the results of learning management by using the achievement tests with 30 students. The fourth phase’s objective is to certify the system based on the system assessment by five experts. Research findings are as follows: 1. The current situation of and need for blended instructional system using problem-based learning to enhance higher thinking skills and problem-solving ability in science for secondary school students as a whole is at a high level; 2. The system developed in this study consists of five components, namely (1) analysis, (2) design, (3) execution of learning activities, (4) evaluation, and (5) feedback; 3. Results of the use of instructional system reveal that the students’ learning achievement is improved at the significance level of .01. A comparison of relationship between learning achievement and measurement of higher thinking skills after application of the blended learning reveals that the two factors have the highest relationship at the significance level of .01. Furthermore, students’ overall satisfaction is at the highest level; and 4. With regard to experts’ opinion on the blended instructional system using problem-based learning to enhance higher thinking skills and problem-solving ability in science for secondary school students, quality of the blended instructional system is at a high level and the experts have certified the system.